2003
DOI: 10.1159/000070647
|View full text |Cite
|
Sign up to set email alerts
|

The Lowest Diploid Number (2n = 16) yet Found in Any Primate: Callicebus lugens (Humboldt, 1811)

Abstract: Morphologic, molecular and karyologic analyses of Callicebus lugens (Humboldt, 1811) of known geographic origin supported the proposition that this is a valid species. Morphologic and morphometric analyses showed evident differences between C. lugens and two other related taxa of the same group (Callicebus purinus and Callicebus torquatus). Cytochrome b DNA analyses (maximum parsimony, neighbour joining and maximum likelihood) were congruent in showing a strong association between C. lugens and Callicebus sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
9
0
4
Order By: Relevance
“…41) to 2n ϭ 16 (Callicebus lugens; ref. 42). However, in this case, detailed cytogenetic analysis by using FISH shows that despite the diversity and the rearranged karyotype, the synteny of 11 human chromosomes is maintained intact in Callicebus callicebus (43).…”
Section: Discussionmentioning
confidence: 99%
“…41) to 2n ϭ 16 (Callicebus lugens; ref. 42). However, in this case, detailed cytogenetic analysis by using FISH shows that despite the diversity and the rearranged karyotype, the synteny of 11 human chromosomes is maintained intact in Callicebus callicebus (43).…”
Section: Discussionmentioning
confidence: 99%
“…Collecting sites, morphological traits, and karyotypic description of the C. lugens samples used here for chromosome painting were recently described (Bonvicino et al 2003). Briefly, metaphase preparations were obtained from bone marrow cultures from four wild, caught C. lugens after a brief culture.…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetic studies have shown that New World primates are karyologically diverse, and some species are highly derived with respect to the chromosome complement of humans or a presumed platyrrhine ancestor (Chu and Bender 1962;Koiffmann and Saldanha 1981;Consigliere et al 1996Consigliere et al , 1998Stanyon et al 2000;Bonvicino et al 2003). The genus Callicebus is one of the best examples of this diversity because diploid numbers among species range from 2n=50 (Rodrigues et al 2001) to 2n=16 (Bonvicino et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Roosmalen et al (2002) recognized 28 species arranged in five species groups (donacophilus, moloch, cupreus, torquatus and personatus) while karyologic studies showed a wide spectrum of variation in diploid chromosome number, ranging from 2n = 50 in C. hoffmannsi to 2n = 16 in C. lugens, the species with the lowest diploid number in the primate order ( Fig. 5; Bonvicino et al, 2003b). While molecular studies associated Callicebus with Pithecia, Cacajao and Chiropotes, it has been so far impossible to clearly link Callicebus to any other platyrrhine genus by phylogenetic reconstructions based on comparative karyology.…”
Section: Pithecid Radiation: Molecular and Cytogenetic Datamentioning
confidence: 99%